Conflict Displacement and Labor Market Outcomes in Post-war Bosnia and Herzegovina - Kondylis, Florence (2012)
The war in Bosnia and Herzegovina of the early nineties displaced 1.3 million people. This study uses longitudinal data to document the effects of this displacement on labor market outcomes. To account for endogeneity in displacement, I exploit the fact that the level of violence affected the decision to leave and that pre-war economic performance is orthogonal to local violence levels. I find that displaced Bosnians are less likely to be working relative to the people who stayed. Displaced men experience higher unemployment levels, and displaced women are more likely to drop out of the labor force.